2022
DOI: 10.1029/2022gl100555
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of the Ionosphere Caused by the 2022 Tonga Volcanic Eruption Observed With SuperDARN Radars

Abstract: submarine volcano (hereafter referred to as the Tonga volcano), which is centered at 20.546°S, 175.390°W, explosively erupted. Immense ripples on the sea surface and in the atmosphere rapidly spread outward. The volcanic explosivity index (VEI) was estimated to be 6, indicating that this eruption was one of the largest volcanic eruptions recorded in the modern era (Poli & Shapiro, 2022). The volcanic eruption released a large amount of material and energy into the atmosphere, with the highest overshooting tops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The considerably fast response of the ionosphere to the arrival of the atmospheric disturbances cannot be fully explained by the forward energy leakage of the acoustic waves in the thermosphere. In this context, recent studies on traveling ionospheric disturbances just after the Tonga volcanic eruption have reported that the ionospheric disturbances appeared in the Northern and Southern Hemispheres with magnetic conjugacy (42)(43)(44)(45). The generation mechanism of the ionospheric disturbances is somehow an instantaneous transmission of the electric field to the magnetic conjugate ionosphere along the magnetic field lines (44).…”
Section: Spatial Distribution Of Time Difference Between Ionospheric ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The considerably fast response of the ionosphere to the arrival of the atmospheric disturbances cannot be fully explained by the forward energy leakage of the acoustic waves in the thermosphere. In this context, recent studies on traveling ionospheric disturbances just after the Tonga volcanic eruption have reported that the ionospheric disturbances appeared in the Northern and Southern Hemispheres with magnetic conjugacy (42)(43)(44)(45). The generation mechanism of the ionospheric disturbances is somehow an instantaneous transmission of the electric field to the magnetic conjugate ionosphere along the magnetic field lines (44).…”
Section: Spatial Distribution Of Time Difference Between Ionospheric ...mentioning
confidence: 99%
“…Various kinds of geophysical phenomena generated by the largest-on-record January 15, 2022 Tonga eruption have been previously recorded in a global dataset consisting of atmospheric waves (23,46), tsunamis (47), and ionospheric disturbances (24)(25)(26)(27)(28)(29)(30)(42)(43)(44)(45), thereby providing a unique opportunity for an integrated study based on the synergy of multi-disciplinary observation data. This study provides clear evidence of the EPB appearance after the Tonga volcanic eruption, thereby corroborating the existence of a seed effect of atmospheric disturbances, as anticipated by previous studies (28).…”
Section: Spatial Distribution Of Time Difference Between Ionospheric ...mentioning
confidence: 99%
“…(2022) pointed out that the depletion of local TEC measurements could reach as high as 10–15 TEC Unit (TECU). Volcano effects manifested in the range‐time‐intensity plots of the Super Dual Auroral Radar Network observations as rapid oscillations in the line‐of‐sight Doppler velocities (J. Zhang et al., 2022). In situ ion density and drift measurements from the Ion Velocity Meter onboard ICON also showed clear signatures of GW impacts (Gasque et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The Hunga Tonga‐Hunga Ha'apai volcano's series of eruption events on the 15 January 2022, have found interest from a broad range of scientific communities, from solid Earth and ocean dynamics (Carvajal et al., 2022; Kubota et al., 2022; Poli & Shapiro, 2022), to ground‐based infrasound (Chunchuzov et al., 2023; Matoza et al., 2022), and to aeronomy and space physics (e.g., Wright et al., 2022; Themens et al., 2022; S.‐R. Zhang et al., 2022). This event provided a unique opportunity to advance our understanding of NH‐induced waves from a large‐magnitude source.…”
Section: Introductionmentioning
confidence: 99%
“…Estimated as a megatons‐equivalent event (Matoza et al., 2022; Vergoz et al., 2022), the eruptions generated a very broad spectrum of waves that propagated globally over several days (S.‐R. Zhang et al., 2022). The reports suggest complex and nonlinear AGW dynamics in the atmosphere, impacting the state of the stratosphere (Khaykin et al., 2022; Millan et al., 2022) and ionosphere (Astafyeva et al., 2022; Harding et al., 2022; He et al., 2023; Li et al., 2023; Vadas et al., 2023a), generating effects locally and in the magnetically‐conjugate ionosphere via coupling through the plasmasphere (Aa et al., 2022a; Harding et al., 2022; Lin et al., 2022).…”
Section: Introductionmentioning
confidence: 99%